High sensitivity cardiac troponin T is a useful biomarker for predicting prognosis of the patients with sarcoidosis. (25th November 2020) - Baba, Y; Kubo, T; Kawaguchi, J; Ochi, Y; Hirota, T; Yamasaki, N; Kitaoka, H
Abstract: Background: Cardiac involvement is one of the most significant prognostic factors for the patients with sarcoidosis. In spite of the advancement of diagnostic tools, such as cardiac magnetic resonance imaging or 18F-fluoro-2-deoxyglucose positron emission tomography, there is still significant room for improvement in cardiac screening and prognostic prediction. Purpose: To evaluate the prognostic factors for the patients with sarcoidosis. Methods and results: We prospectively studied 133 patients with sarcoidosis and evaluated clinical data including biomarkers. The mean age at diagnosis was 62.1±12.8 years. During a mean follow up period of 5.6±4.1 years, nine patients died and 27 patients suffered from cardiac events (cardiac death, heart failure admission, arrhythmic event). We divided patients into two groups according to cardiac events, event group had high serum high-sensitivity cardiac troponin T (hs-cTnT) (0.028±0.017 vs. 0.015±0.011 ng/ml, p<0.001), high BNP (409.2±634.0 vs. 122.4±195.8 pg/ml, p<0.001), low EF (43.1±16.4 vs. 59.2±15.5%, p<0.001). This was observed even if those patients were not diagnosed with cardiac involvement at the enrollment. On the other hand, there were no significant differences in the values of angiotensin-converting enzyme, lysozyme, soluble interleukin-2 receptor, or calcium in both groups. Multivariate analysis revealed that hs-cTnT was an independent biomarker to predict cardiac events (hs-cTnT >0.014 ng/ml: HR 3.2, 95% CI 1.02 to 10.19, p=0.046). Conclusion: Hs-cTnT was a useful biomarker for predicting cardiac events for the patients with sarcoidosis even if cardiac involvement was not detected at initial evaluation. Funding Acknowledgement: Type of funding source: None